Urine pH and Uric Acid Metabolism in Patients with Gout - KAGAWA, Daizaburo; UCHIDA, Michihiko; KUBO, Akemi; ANDO, Seisho; DOMAE, Naochika; SASADA, Masataka; HARA, Akira; NAKAMURA, Toru; TSUTANI, Hiroshi; UEDA, Takanori; UCHINO, Haruto (Uric acid research, 1983)
To clarify the relationship between acidity of urine and uric acid metabolism, especially under excretion of urate, urine pH was determined before each meal in 139 gouty patients for 2-4weeks. Urine pH was correlated with urate metabolism coefficients such as serum urate level (Sua), urinary excretion (Uua), urate clearance (Cua), creatinine clearance (Ccr) and clearance ratio (R) as determined by the urate clearance test previously reported. The ratio of patients with acidic urine w as higher in the group with severe under excretion than in that with overproduction, but no significant correlation was observed between the urate metabolism coefficients and urine pH in these patients(X25.2<X20.05=15.5). Administration of 3.0 gr of Uralyt U daily caused a significant increase in urine pH (P<0.01) which was of a lesser grade in the morning urine, but no evidence of increasing urate excretion was found. In daily profile of urine pH in a normal subject, urine pH was low before meals especially before breakfast but a transient increase was seen 2-3 hours after meals, probably due to the acid-base balance of the administered diet.